Statistical analysis and molecular dynamics simulations of the thermal conductivity of lennard–Jones solids including their pressure and temperature dependencies - Heyes,DM; Dini,D; Smith,ER (Physica Status Solidi B: Basic Solid State Physics, 2020)
Aspects of the thermal conductivity, λ, of a Lennard–Jones (LJ) solid along an isotherm and the sublimation line are studied using equilibrium molecular dynamics (MD) simulations. A reformulation of the Green–Kubo time correlation function expression for λ in the form of a probability distribution function (PDF) of single trajectory contributions (STC) exhibits the same characteristic statistical trends as found previously for liquids, even at high pressures and low temperatures. The analysis reveals that for short periods of time the thermal conductivity can be negative. This feature is evident along the sublimation line isobar and a lowtemperature isotherm going to high densities. Along the isobar and isotherm lines, λ is to a good approximation a power law in temperature and density, respectively. This behavior is used in a more general thermodynamicsbased analysis description of the state point dependence of the thermal conductivity. The heat flux autocorrelation function increasingly develops a damped oscillatory appearance as pressure increases or temperature decreases, consistent with the phonon formulation of thermal conductivity.